Pengaruh Back Massage Terhadap Tingkat Nyeri Low Back Pain pada Kelompok Tani Semangka Mertha Abadi di Desa Yeh Sumbul - Kusuma Dewi, Ni P P; Sutresna, I Nyoman; Susila, I Made Dwie Pradnya (Journal Center of Research Publication in Midwifery and Nursing, 2017)
Low back pain is one of the musculoskeletal problems due to worse activity and causes the incurrence of sore, pain, and hurt. Pain management can be surmounted by non-pharmacological therapy through back massage. Back massage is a technique of giving massage on the back with smooth swab. This study aimed at knowing the influence of back massage towards the low back pain level to the Mertha Abadi watermelon farmers group. This study was pre experimental research, with one group pretest-posttest design. Sample consisted of 30 members of watermelon farmers which were chosen through purposive sampling. The data was analyzed with statistical test using Wilcoxon Signed Rank Test with the result obtained that p value 0,001 was less than Î±=0,05 (p<0,05) meant Ho was rejected and the hypotheses in this study was accepted, therefore it could be concluded that there was a significant influence of back massage towards the low back pain level to the Mertha Abadi watermelon farmers group in Yeh Sumbul village. Based on the result of this study, back massage is really needed to be applied in order to reduce pain to the low back pain patients.